Charge and mass transport mechanisms in two-dimensional covalent organic frameworks (2D COFs) for electrochemical energy storage devices - Zhang, Hanyin; Geng, Yubo; Huang, Jin; Wang, Zixiao; Du, Kun; Li, Haoyuan (Energy & environmental science, 2023)
The development of smartphones and electric cars calls for electrochemical energy storage devices with higher capacities, faster charging rates, and improved safety. A key to developing these devices is the discovery of better electrode and electrolyte materials. Over the past few years, a new type of organic materials, two-dimensional covalent organic frameworks (2D COFs), have attracted increasing attention and are explored as both electrode and electrolyte materials in energy storage devices such as metal-ion batteries, metal batteries, and supercapacitors. Indeed, the intriguing features of the nanoscale porous structure of 2D COFs and their tunable functionalities have brought many new possibilities to the already vibrant field of electrochemical energy storage materials. The performances of electrochemical energy storage devices are largely determined by two fundamental processes: charge and mass (ion) transport. Both processes carry the flow of charges but with different microscopic mechanisms. A good understanding of these processes is essential to accelerate the development of 2D COFs in electrochemical energy storage devices. However, the unique characteristics of 2D COFs result in complex charge and mass transport mechanisms, creating a barrier for new researchers to enter this field. Here, we provide a state-of-the-art overview of recent studies into this subject as well as a summary of the fundamental elements of charge and mass transport in 2D COFs for energy storage applications. The paths of 2D COFs for energy storage devices are also discussed. We believe that this review will be helpful to researchers interested in working on 2D COFs and electrochemical energy storage applications. Understanding charge- and mass-transport processes in two-dimensional covalent organic frameworks to design better materials and energy storage devices.